A model of the general circulation in the Persian Gulf and in the Strait of Hormuz: Intraseasonal to interannual variability. (15th February 2015) - Pous, Stéphane; Lazure, Pascal; Carton, Xavier
Abstract: Previous studies modeling the circulation and thermohaline structure in the Persian Gulf have suggested that interannual variability and vertical mixing processes could explain the model biases when compared to the few observations available. Here, a realistic, interannual, high-resolution model of the Persian Gulf is presented, validated against observations and then used to describe the intraseasonal to interannual variability in the circulation, water mass formation and exchange through the Strait of Hormuz. Sensitivity experiments to model settings, in particular vertical mixing parameterizations, have been performed in order to have the best comparison with all available observations. Main circulation and water mass characteristics correspond well to observations and previous modeling studies on the seasonal timescale. A barotropic cyclonic gyre dominates the general circulation in the Gulf from April to July then breaks down into smaller features as wind intensifies and stratification decreases due to winter cooling. Dense salty water is formed in the northwest part of the Gulf and in the southern banks, but the latter reaches the Strait of Hormuz from November to April only. While temperature fluctuations are mostly seasonal, salinity has substantial fluctuations on the interannual timescale that cannot be directly related to atmospheric fluxes because of the importance of the exchanges at Hormuz for the salt budget within the Gulf. This advocates the use of atmospheric conditions including interannual variations when running models of the Persian Gulf. On the other hand, the interannual variations in the net transport at Hormuz directly follow variations in the evaporation minus precipitation over the Gulf. Thermohaline structure and circulation also vary on intraseasonal timescale, induced by the high-frequency tidal and atmospheric forcings. Finally, some biases remain in the simulations presented here, mostly due to the lack of observations of the evaporation rate, precipitation and river discharges. Abstract : Highlights: Currents and thermohaline structure in the Persian Gulf are realistically modeled. The seasonal variability of circulation and water mass formation is re-produced. The interannual variability is related to surface fluxes and salty water formation. On the long term, the transport at Hormuz follows evaporation–precipitation.